2019
DOI: 10.1042/cs20181088
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus-induces progression of lung disease in a mouse model of COPD via IL-33/ST2 signaling axis

Abstract: Rhinovirus (RV), which is associated with acute exacerbations, also causes persistent lung inflammation in patients with chronic obstructive pulmonary disease (COPD), but the underlying mechanisms are not well-known. Recently, we demonstrated that RV causes persistent lung inflammation with accumulation of a subset of macrophages (CD11b+/CD11c+), and CD8+ T cells, and progression of emphysema. In the present study, we examined the mechanisms underlying the RV-induced persistent inflammation and progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Macrophages are innate immune cells that play a critical role in resolving inflammation and defending against exogenous pathogens, contributing to lung homeostasis. 3 , 4 Macrophages are classified as classically activated (M1) or alternatively activated (M2). 5–7 M1 macrophages are induced by interferon-γ (IFN-γ) and lipopolysaccharide (LPS), produce inducible nitric oxide synthase (iNOS) and tumor necrosis factor α (TNF-α), and exert proinflammatory and cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are innate immune cells that play a critical role in resolving inflammation and defending against exogenous pathogens, contributing to lung homeostasis. 3 , 4 Macrophages are classified as classically activated (M1) or alternatively activated (M2). 5–7 M1 macrophages are induced by interferon-γ (IFN-γ) and lipopolysaccharide (LPS), produce inducible nitric oxide synthase (iNOS) and tumor necrosis factor α (TNF-α), and exert proinflammatory and cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages are innate immune cells that play a key role in alleviating inflammation and defending against invasion by external pathogens (66,67). Studies found that macrophage activation is closely related to the occurrence of COPD, and the total number of macrophages is proportional to the severity of smoking and COPD (68).…”
Section: Role Of Ferroptosis In Copdmentioning
confidence: 99%
“…Next, we examined whether DPP4 expression is associated with NTHi-induced lung inflammation in vivo by using mice displaying mild to moderate COPD-like lung disease (27,32,33). Our previous studies demonstrated that normal mice clear all the bacteria by 3 days postinfection and resolve bacteria-induced inflammation by day 7 (27,30).…”
Section: Nthi-infected Copd Mice Show Sustained Lung Inflammation and Increased Dpp4 Expressionmentioning
confidence: 99%